New X linked spondyloepimetaphyseal dysplasia: report on eight affected males in the same family. Issue 5 (May 1994) - Camera, G; Stella, G; Camera, A
Abstract : We report on a probably new form of spondyloepimetaphyseal dysplasia (SEMD) with an X linked inheritance pattern. Eight males were affected in the same family. We were able to examine three adult patients and we studied the skeletal radiological aspect of one of these patients at 2 years 6 months and at 9 years of age. The main clinical features are severe short trunked dwarfism, brachydactyly, normal facies, and normal intelligence. Radiologically, the diaphyses of all the long bones are short and broad. The epiphyses of the distal portion of the femora and those of the proximal and distal portions of the tibia are embedded in their metaphyses and there is marked narrowing of the intercondylar groove. There is moderate platyspondyly. Several vertebrae show an anterior tongue in infancy and severe irregularities of the upper and lower surfaces are present in adulthood. The 11th or 12th thoracic vertebra is wedge shaped. The pelvis is narrow. The distal ulnae and fibulae are disproportionately long. The hands show radial deviation and brachydactyly is present in the hands and feet. This X linked SEMD was not detectable at birth.